Economics Impacts of Cross-Border Tourism - CHANCHARAT, Surachai; SOMSAWAS, Jintana (Journal of Environmental Management and Tourism, 2016)
In this paper, we analyze the impacts of Thai-Laos cross-border tourism to employment in Nakhonphanom, Thailand with the expenditure data of the respondents who come to important attractive places of this province. The inter-industry linkages of the 16 economic sectors for 2012 were analyzed using the Input-Output model. The study shows that the total expenditure on the trip can separate into 6 sections. The major expenditure of visitors is accommodation, followed by food and beverages, local transportation, shopping and retail trade, recreational activities and tourism service. The average expense of tourist was approximately 220.24 USD per trip per person. The analysis of the impact of the tourism industry to employment in Nakhonphanom shows that the spending of tourists can cause the total employment in Nakhonphanom province of 30,179 persons and it causes the direct employment lowers than the indirect employment. The most employment is from the service sector and the others are from the agricultural sector and industry sector, respectively. The result finds that the major cause of the impact of the expenditure on employment is the expenditure for the service as hotels and restaurants.
Keywords: employment; input-output analysis; Thailand; Laos